Implementasi Pendidikan Kewarnegaraan Berbasis Nilai-Nilai Pancasila Melalui Pembiasaan Untuk Menumbuhkan Karakter Siswa di Sekolah Dasar - Dewi Nurhasanah Nasution (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2023)
The lack of habituation of Pancasila values ​​in implementing citizenship education will cause the morals or morals and character of elementary school children not to be in accordance with Pancasila values ​​that have been taught in citizenship education subjects as a form of implementation. This research is based on literature study. The type of research used is descriptive qualitative critical, namely with more emphasis on the ability to analyze and study the selected literary sources. The results showed that the implementation of citizenship education based on Pancasila values ​​through habituation to cultivate character in elementary schools was carried out by getting students to pray before and at the end of learning, mutual respect for teachers, tolerance, not discriminating between friends based on their religion, not bullying friends, loving each other. and respect fellow human beings, accustomed to making decisions by deliberation, making friends with anyone.